(untitled) (Modern education and development, 2025)
This paper investigates effective pedagogical approaches to teaching paragraph and essay organization to B2-level English as a Foreign Language (EFL) learners. It highlights the importance of guiding students through the transition from constructing accurate sentences to developing coherent and logically structured texts. Particular attention is given to the instruction of topic sentences, supporting details, and cohesive devices. Drawing on both theoretical perspectives and practical classroom experiences, the study proposes a step-by-step model aimed at improving learners’ academic writing skills. The findings suggest that systematic instruction combined with scaffolded writing tasks enhances students’ ability to produce well-organized written texts at the intermediate level.